2009
DOI: 10.1176/ps.2009.60.7.943
|View full text |Cite
|
Sign up to set email alerts
|

Help Seeking and Perceived Need for Mental Health Care Among Individuals in Canada With Suicidal Behaviors

Abstract: Although suicidal ideation and suicide attempts represent a significant source of evaluated need associated with help seeking and perceived need over and above the presence and severity of mental disorders, a significant proportion of individuals with suicidal behaviors did not receive care and did not perceive a need for care. Future research should be directed toward finding better ways to identify these individuals and address barriers to their care and other factors that may interfere with their receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 32 publications
1
32
1
Order By: Relevance
“…Finally, the current study found that 4.3% of participants reported past-year SI. A nationally-representative study of the Canadian general population found a past-year SI rate of approximately 3.3% [53], while data from the US military’s Post-Deployment Health Assessment survey found that 1.3% of participants reported “some” to “a lot” of SI [51]. Similarly to mental health disorders, SI may be susceptible to underreporting in actively serving military populations for a number of reasons (“healthy soldier” effect, fears about job security, stigma, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study found that 4.3% of participants reported past-year SI. A nationally-representative study of the Canadian general population found a past-year SI rate of approximately 3.3% [53], while data from the US military’s Post-Deployment Health Assessment survey found that 1.3% of participants reported “some” to “a lot” of SI [51]. Similarly to mental health disorders, SI may be susceptible to underreporting in actively serving military populations for a number of reasons (“healthy soldier” effect, fears about job security, stigma, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, few adolescents with mental health problems independently seek help from formal helpers such as school counselors (Husky et al, 2010), and most teens seek help only from their peers (Raviv et al, 2009). Low help seeking from adults is more pronounced among adolescents with suicidal thoughts or behavior, with SI associated with reduced help seeking among adolescents compared to those with a mental health condition alone (Pagura et al, 2009). Therefore understanding factors that facilitate or inhibit suicidal adolescents from seeking out adults is an important topic for research.…”
Section: Disclosure and Receiving Helpmentioning
confidence: 99%
“…[22] Data on suicidal ideation supports that depressed patients with suicidal thoughts more actively seek care then those who do not have suicidal thoughts. [23] Increased education levels are associated with greater care seeking behaviors, potentially implying that the inability to properly self-identify depression (particularly in mild to moderate cases where symptoms may not be as obvious) may be a possible barrier. [24]…”
Section: Introductionmentioning
confidence: 99%